SISTEM INFORMASI PENGGAJIAN PEGAWAI PADA DINAS TENAGA KERJA KOTA BANDUNG - Cyntia Rivatunisa (INFOKOM (Informatika & Komputer), 2022)
Information is currently increasing along with technological developments, as well as the need for information on employee payroll at the Bandung City Manpower Office. However, in its implementation, employee payroll information is still experiencing problems such as presenting employee data and salary data which takes a long time and sometimes there is a delay in data search and slow processing of salaries and also results in slow report generation. This research aims to build an Employee Payroll Information System at the Bandung City Manpower Service so that it can assist related parties in obtaining accurate, fast and accurate information. The method of data collection by the author uses interviews, observation, and documentation studies. In system development, the author uses the Prototyping approach. For database design used normalization method, table relation, and entity relation diagram. Implementation and design of the program using the Visual Basic 6.0 programming language and MySQL database. Based on the results of the study, it can be seen that the employee payroll information system at the Bandung City Manpower Service is still experiencing problems, due to many weaknesses in ongoing data processing, such as the presentation of employee data and salary data takes a long time and sometimes there are delays in searching data and slow processing of salaries and also resulted in slow report generation.